Autologous Tenon’s patch graft: Techniques, clinical outcome, and complications in cases of immune corneal melt - Nisha Rani; Srikant K Sahu; Sonali Sahoo (Indian Journal of Ophthalmology)
Purpose: To study the techniques, clinical outcomes, and complications of autologous Tenon’s patch grafting in patients with non-infectious corneal melt. Methods: This retrospective analysis included 15 eyes from 15 patients with non-infective corneal melt who underwent autologous Tenon’s patch grafting between January 2021 and December 2023 at our tertiary care institute. The age of the patients ranged from 16 to 79 years (mean: 46.64 ± 17.20 years), and there were eight males and seven females. Tenon’s tissue was harvested from the same eye in all patients, placed on the perforation site, and tucked in and secured with 10-0 nylon sutures in 14 eyes and with additional cyanoacrylate glue in one eye. The follow-ups ranged from 1 month to 2 years (mean: 9.17 ± 6.83 months). Results: The graft healed with scarring and vascularization in 10 eyes (66.67%), and loss of Tenon’s patch graft was seen in two eyes (13%). Three (20%) patients were lost to follow-up, and five (33%) achieved a vision of >20/200. Conclusion: In active immune corneal melt, Tenon’s patch graft restores cornea and globe integrity, delaying the need for keratoplasty in an inflammatory condition.